Silicon attenuates abiotic stress caused by ammonium toxicity but not nitrogen deficiency in cotton plants - Leal, Aguinaldo Jose Freitas (2021)
Although N - NO3- predominates in many soils, compared to N - NH4+, the fluctuations in the forms and concentrations of N can expose to N deficiency in plants in general and NH4+ toxicity in NH4+ sensitive plants. However, a strategy to mitigate nutritional disorders of N is to utilize Si. We aimed to verify if Si attenuates N deficiency and NH4+ toxicity in cotton plants grown in nutrient solution. The treatments followed a 5 x 2 factorial scheme, with five concentrations of NH4+ (1.0; 7.5; 15.0; 22.5 and 30.0 mmol/L) combined with the absence and presence of Si (1 mmol/L), arranged in a completely randomized design with four replications. Without Si, the largest shoot dry mass occurred at 16 mmol/L NH4+, increased by 47%, compared to 1 mmol/L NH4+ and decreased by 37% compared to 30 mmol/L NH4+. With Si, the largest shoot dry mass was observed at 20 mmol/L NH4+, increased by 52% compared to 1 mmol/L NH4+ and decreased by 14% compared to 30 mmol/L NH4+. In addition, in the highest concentration of NH4+, plants with Si exhibited a higher shoot dry mass relative to plants with no Si supplementation due to decreased electrolyte leakage index and increased use efficiency of N and K. Cotton plants were tolerant to high NH4+ concentrations (approximate to 15 mmol/L). Si attenuates abiotic stress caused by NH4+ toxicity (30 mmol/L) but not N deficiency in cotton plants.